Urban void as a potential of the contemporary city development - Pluta, Agata (Pustka przestrzenna jako potencjał rozwoju współczesnego miasta, 2017)
A city is a cluster of buildings and areas of activity. The spaces between urban structures are often treated as a side effect, an accidental phenomenon present due to the location of buildings. However, in contrast to the buildings that have their functions established once they are erected, urban voids contain the potential for rapid change of use constituting an important element of both planned and unplanned activities. Empty spaces are possibilities for future arrangements and evolution of needs that are often unknown at the time of construction. The main objective of the article is to define the concept of ‘urban void’ and to analyze the hidden potential of it. The author emphasizes the need to create empty spaces as deliberately as architecture itself, including them in the urban tissue
Biblioteka Regionalisty, 2017, Nr 17, s. 95-104
Keywords: urban void; temporary use; city; urban planning; potential; adaptability; pustka przestrzenna; tymczasowe użytkowanie; miasto; planowanie urbanistyczne; potencjał; adaptacyjność